Does a Renewable Fuel Standard for Biofuels Reduce Climate Costs? - Mads Greaker; Michael Hoel; Knut Einar Rosendahl (Fondazione Eni Enrico Mattei (FEEM), 2014)
Recent literature on biofuels has questioned whether biofuels policies are likely to reduce the negative effects of climate change. In this paper we make two contributions to the literature. First, we study the market effects of a renewable fuel standard in a dynamic model taking into account that oil is a non-renewable resource. Second, we model emissions from land use change explicitly when we evaluate the climate effects of the renewable fuel standard. We find that global extraction of oil is postponed as a consequence of the renewable fuel standard. Thus, if emissions from biofuels are negligible, the standard will have beneficial climate effects. Furthermore, we find that the standard also tends to reduce total fuel (i.e., oil plus biofuels) consumption initially. Hence, even if emissions from biofuels are non-negligible, a renewable fuel standard may still reduce climate costs. In fact our simulations show that even for biofuels that are almost as emissions-intensive as oil, a renewable fuel standard has beneficial climate effects.
Keywords: Q27; Q41; Q54; 330; Blending Mandate; Renewable Fuel Standard; Biofuels; Climate Costs